Navigator‐based reacquisition and estimation of motion‐corrupted data: Application to multi‐echo spin echo for carotid wall MRI. Issue 6 (7th November 2019) - Frost, Robert; Biasiolli, Luca; Li, Linqing; Hurst, Katherine; Alkhalil, Mohammad; Choudhury, Robin P.; Robson, Matthew D.; Hess, Aaron T.; Jezzard, Peter
Abstract : Purpose: To assess whether artifacts in multi‐slice multi‐echo spin echo neck imaging, thought to be caused by brief motion events such as swallowing, can be corrected by reacquiring corrupted central k‐space data and estimating the remainder with parallel imaging. Methods: A single phase‐encode line ( ky = 0, phase‐encode direction anteroposterior) navigator echo was used to identify motion‐corrupted data and guide the online reacquisition. If motion corruption was detected in the 7 central k‐space lines, they were replaced with reacquired data. Subsequently, GRAPPA reconstruction was trained on the updated central portion of k‐space and then used to estimate the remaining motion‐corrupted k‐space data from surrounding uncorrupted data. Similar compressed sensing‐based approaches have been used previously to compensate for respiration in cardiac imaging. The g‐factor noise amplification was calculated for the parallel imaging reconstruction of data acquired with a 10‐channel neck coil. The method was assessed in scans with 9 volunteers and 12 patients. Results: The g‐factor analysis showed that GRAPPA reconstruction of 2 adjacent motion‐corrupted lines causes high noise amplification; therefore, the number of 2‐line estimations should be limited. In volunteer scans, median ghosting reduction of 24% was achieved with 2 adjacent motion‐corrupted lines correction, and image quality was improved in 2 patient scans that had motion corruption close to the center of k‐space. Conclusion: Motion‐corrupted echo‐trains can be identified with a navigator echo. Combined reacquisition and parallel imaging estimation reduced motion artifacts in multi‐slice MESE when there were brief motion events, especially when motion corruption was close to the center of k‐space.